The Laws of Solon. A New Edition with Introduction, Translation and Commentary - Leão, Delfim (2015)
Solon (c 658-558 BC) is famous as both statesman and poet but also, and above all, as the paramount lawmaker of ancient Athens. Though his works survive only in fragments, we know from the writings of Herodotus and Plutarch that his constitutional reforms against the venality, greed and political power-play of Attica's tyrants and noblemen were hugely influential-and may even be said to have laid the foundations of western democracy. Solon's legal injunctions covered the widest range of topics and issues: economics and labour; sexual morality; social issues; and society and politics. Yet despite their fame and influence (and Solon's life and work generated a lively reception history), no complete edition of these writings has yet been published. This book offers the definitive critical edition of Solon's laws that has long been needed. It comprises the original Greek fragments with English translations, commentaries, a comprehensive introduction and important comparative Latin texts. It will be enthusiastically welcomed by specialists in ancient Greek language and history.